OPTIMASI PENGISIAN BOTOL DENGAN PROPORTIONAL WATER VALVE SYSTEM BERBASIS KENDALI OTOMATIS - I Putu Oka Sutrisna; I Gusti Ngurah Adia Atmika (Jurnal Bakti Saraswati (JBS), 2024)
In both small and large-scale industries, automation plays a critical role in improving system efficiency and optimization. This is especially true in the bottled water industry, where the adoption of automation systems has become increasingly essential. Traditional systems that rely on manual controls, such as valve openings, machine timing, and gravity, are often inaccurate when filling bottles. This research focuses on optimizing the bottle-filling process using a proportional water valve system based on automatic control. The automation system consists of three main components: input, process, and output. The study's results indicate that this innovative system can accurately calculate the amount of water needed for bottle filling, significantly reducing wastage. Tests showed that the difference between theoretical values and actual measurements had a minimal error, with an average time of 6,5 seconds to fully fill a bottle. The system operates by adjusting the valve opening through a krone valve, controlled by flow rate sensors, ensuring a more accurate and efficient water filling process, particularly for PET bottle products.